Optimization of low-grade tetragonal zirconia by praseodymium oxide additions - Labrincha, António (2022)
Zirconia-based materials are still the state of art electrolyte for high temperature electrochemical systems, and for non-electrochemical applications. Their purity is known to affect performance, thus requiring high-grade expensive precursors and additional concerns about contamination during high temperature processing and/or during long term applications at intermediate temperatures, as found for contamination by silica. Thus, the purpose of this work was to demonstrate the scavenging ability of praseodymium oxide to minimize or suppress the impact of contamination by silica. In the present work, one used TZP precursor powders from Tosoh and Innovnano. Starting materials of both powders contained significant fractions of monoclinic phase, coexisting with tetragonal zirconia, and yielded highly dense samples after sintering at 1450°C/2h. Praseodymium oxide and/or silicon oxide additions did not affect significantly the sintering behaviour. Additions of Pr and Si yielded co-existing tetragonal and cubic phases, as revealed by XRD and Rietveld refinements, with an impact on lattice parameters of the cubic phase. The electrical characterization showed the expected severe decrease in conductivity after the addition of silicon oxide addition and also showed that this negative impact is at least partially reverted by additions of praseodymium oxide.